Strategi Manajemen Perubahan di Perusahaan Agar dapat Bertahan di Era Digital “Studi Kasus PT Era Surya Ritelindo” - Habib Lauda Nararya; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
The development of digital technology has provided major and fundamental changes in various aspects of life as well as business organizations. This article aims to discuss change management strategies in companies in order to survive in the digital era. The research approach that will be used in this research is a descriptive qualitative approach. The method of data collection in this study was the data collection technique by means of interviews. Data will be collected from known company relationships and search for various documents and articles and then relate them to the theories that have been collected. The author sees that there are changes in the Kasimura Supermart company which after adapting to digital the company's development has a positive impact.